Importance of the eCG-hCG injection interval for superovulation, fertilization, and embryonic development in rats - Yuki Nakagawa; Takehito Kaneko (Heliyon)
Superovulation is an essential reproductive technique to obtain many oocytes. In rats, superovulation is induced by equine chorionic gonadotropin (eCG) injection, followed by human chorionic gonadotropin (hCG) injection after approximately 48 h. However, some strains, such as the Brown Norway (BN) strain, do not respond to this protocol, indicating that the optimal eCG-hCG injection interval is different for each strain. Therefore, we aimed to investigate the effects of eCG-hCG injection interval on superovulation in different rat strains. The mean numbers of oocytes from immature and mature BN females treated at injection intervals of 48 and 56 h were low (7.0–10.0 and 6.6–11.0, respectively). However, these numbers increased with hCG injection 72 h after eCG injection (42.7 and 31.2, respectively). The mean number of ovulated oocytes from F344/DuCrlCrlj females increased when the injection interval increased from 48 to 72 h (13.6 vs. 34.3). Notably, many oocytes were obtained from Wistar and F344/Stm females regardless of the injection interval (31.3–37.0 and 50.0–59.5, respectively). We also examined the fertilization and embryonic development of oocytes from BN rats treated at an injection interval of 72 h. In mature females, fertilization rate of oocytes by natural mating was 44 %, and offspring were obtained via embryo transfer (46 %). In immature females, 91 % of oocytes were fertilized via intracytoplasmic sperm injection, and 17 % of the fertilized oocytes developed into offspring. Therefore, sufficient oocytes with normal fertility and developmental ability can be obtained from various rat strains by adjusting the eCG-hCG injection interval.